2019
DOI: 10.18203/2349-3291.ijcp20191044
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of rise in neutrophil to lymphocyte ratio (NLR) and platelet to lymphocyte ratio (PLR) in predicting the mortality in paediatric intensive care

Abstract: Background: When the body is stressed in diverse pathological conditions, it responds by mounting an inflammatory response. Predictive biomarkers reflecting the response may serve as guide to management. Neutrophil to Lymphocyte Ratio and Platelet to Lymphocyte Ratio has been frequently used in adult patients as an indicator for mortality. However, no study has looked into their use within pediatric population. The objective of the study is to assess the prognostic value of rise in NLR and PLR in pediatric int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 31 publications
0
19
0
5
Order By: Relevance
“…Mathews et al 15 in their study found that PELOD-2 >20 predicted mortality in 72.2% patients. Based on the ROC curve, PELOD-2 score >16 predicted mortality with a sensitivity 100% and specificity 54.1%.…”
Section: Discussionmentioning
confidence: 89%
“…Mathews et al 15 in their study found that PELOD-2 >20 predicted mortality in 72.2% patients. Based on the ROC curve, PELOD-2 score >16 predicted mortality with a sensitivity 100% and specificity 54.1%.…”
Section: Discussionmentioning
confidence: 89%
“…They also found PELOD-2 score >20 could predict 72.2% of mortality, and high PLR could predict 77.8% mortality cases. 20 In our study, mean PLR value [77.54 (SD 50.08) vs. 157.13 (67.38); P=0.00] and PELOD-2 score [12 (1.32) vs. 14.65 (SD 2.09); P=0.00 were significantly different between survivors and non-survivors. Another study reported that the percentage of patients with PELOD-2 score >7 was significantly higher in non-survivors compared to survivors (96% vs. 3.6%, respectively; OR=649).…”
Section: Discussionmentioning
confidence: 41%
“…Data have shown that during the early phase of bacterial infection, there is a large increase in the number of platelets in the bloodstream, which then reduces excessively. 12 The lowest lymphocyte value in the sample was 2 and the highest was 39. The patient's lymphocyte mean was 10.3.…”
Section: Discussionmentioning
confidence: 85%
“…Decreased platelet counts in sepsis are associated with an imbalance between central production and peripheral overconsumption of platelets. 11,12 Platelet lymphocyte ratio (PLR) is a value that can be used as a biomarker and can be easily calculated based on a simple laboratory from the results of a complete blood count. The PLR relationship in particular during the systemic inflammatory response was first introduced by Demirag in a patient who had undergone vascular surgery.…”
Section: Introductionmentioning
confidence: 99%